FOCUSING OF 3C144 SOURCE RADIATION BY THE SOLAR CORONA - Galanin, V. V.; Derevjagin, V. G.; Kravetz, R. O. (Одеські астрономічні публікації, 2012)
The research of solar corona by the compact cosmic source radiation was made on URAN-4 radio telescope. In the period from June 6 to June 20 2012 the flow of Crab nebula was measured on the 20 MHz and 25 MHz frequencies. During the eclipse we observe the great increase of 3C144 flow, which is compare with the flow of 3C461 source. Data and results of measurement analysis is presented.